Reducing the risk of transfusion‐transmitted cytomegalovirus infection: a systematic review and meta‐analysis. Issue 6 (29th January 2016) - Mainou, Maria; Alahdab, Fares; Tobian, Aaron A.R.; Asi, Noor; Mohammed, Khaled; Murad, M. Hassan; Grossman, Brenda J.
Abstract : BACKGROUND: Leukoreduced (LR) or cytomegalovirus (CMV)‐seronegative cellular blood components are commonly used to reduce the risk of transfusion‐transmitted CMV infection in high‐risk patients. STUDY DESIGN AND METHODS: We performed a systematic review and meta‐analysis to evaluate the evidence for the use of LR cellular blood components with or without concurrent CMV testing of donor units in patients undergoing chemotherapy or solid organ and hematopoietic stem cell transplantation, in pregnant women, in very‐low‐birthweight infants, and in patients with primary immunodeficiency. We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus from 1980 through February 2015. Studies were included if they had a comparison group. Two independent reviewers selected and appraised studies. Meta‐analysis was performed when appropriate. RESULTS: Of 457 studies screened, 11 were eligible. One study was excluded from the meta‐analysis because the comparison performed differed significantly from the others. Meta‐analysis of five studies that compared leukoreduction to transfusing CMV‐untested blood components showed no significant difference in clinical CMV infection (relative risk [RR], 0.26; 95% confidence interval [CI], 0.04‐1.57) or laboratory CMV infection (RR, 0.33; 95% CI, 0.08‐1.37). Meta‐analysis of three studies that compared leukoreduction to transfusing CMV‐seronegative cellular components showed no significant difference in laboratory CMV infection (RR, 2.18; 95% CI, 0.96‐4.98). Meta‐analysis of two studies that compared adding CMV testing to leukoreduction (vs. leukoreduction alone) showed no significant difference in clinical or laboratory CMV infection. The certainty in estimates was low for all comparisons. CONCLUSION: At present, the scientific evidence does not favor a single strategy for reducing the risk of transfusion‐related CMV infection in high‐risk patients.